Peran Guru dalam Membangun Kepercayaan Diri Siswa dengan Menggunakan Pendekatan Motivasi Intrinsik di Kelas IX UPTD SMPN 3 Salomekko - Suriyati; Syargawir; Jaya Nur, Makmur; Herawati, Herawati; Qadani, Nur (J-SES : Journal of Science, Education and Studies, 2025)
This research intends to describe the function of ninth-grade instructors within enhancing students' intrinsic motivation, especially It seems that you have submitted an incomplete phrase context of issues of the digital age like overreliance on social media and online gaming. The study employs a qualitative method using a descriptive approach. Methods for gathering data involve participant observation and detailed interviews with two ninth-grade teachers, and documentation. The findings indicate that teachers engage in a strategic function in fostering students' inner drive to learn through adaptive teaching approaches, purposeful use of technology, and a supportive classroom environment. Teachers also pay close attention to students' emotional and social conditions, establish positive communication, and promote learning awareness through personal engagement. These strategies have proven effective in minimizing the negative effects of media distractions while encouraging students to remain focused and actively involved in learning. Therefore, the role of the teacher extends beyond merely delivering material-they act as motivators who guide students to reach their full potential